IMF Survey, Volume 30, Issue 16. (IMF Survey; IMF Survey ;, 2001)
The IMF Executive Board announced on August 3 that it had completed the ninth review of Turkey's economic program supported by the three-year Stand-By Arrangement. The Board's decision will enable Turkey to draw SDR 1.2 billion (about USD 1.5 billion) immediately from the IMF. The text of News Brief No. 01/73, as well as a statement issued on July 28 by IMF First Deputy Managing Director Stanley Fischer (see page 262) is available on the IMF's website (www.imf.org).